How to install Boron into aromatic scaffolds: chemistry of diazadiborinines - Kinjo, Rei (2022)
The concept of aromaticity has been of paramount significance in myriad fields of chemistry. To modulate the intrinsic electronic nature of aromatic molecules, partial incorporation of heteroatoms into the benzene scaffold represents a useful strategy in modern inorganic chemistry. This account presents how to incorporate boron into aromatic six‒membered scaffolds, leading to hybrid organic/inorganic benzenes, namely diazadiborinines. In addition, their reactivity towards a variety of substrates are summarized.